What Drives Environmental Disclosure? Evidence from Mining Companies Listed on The Indonesia Stock Exchange - Digdowiseiso, Kumba; Subiyanto, Bambang; Setioningsih, Retno (International Journal of Energy Economics and Policy, 2022)
This study aims to analyse the effects of environmental performance, profitability, and leverage on the environmental disclosure in mining industry sector companies listed on the Indonesia Stock Exchange. The sample of this study was 15 mining companies which were selected by using a purposive sampling technique. We collected the company’s annual report over the period 2014 – 2021. The results showed that environmental performance had a positive and significant effect on environmental disclosure. In this case, the Corporate Performance Rating Program (PROPER) rating was able to prove that there was a significant influence between the Global Reporting Initiative (GRI) as a form of its responsibility and the extent of environmental disclosure. In addition, profitability produced a negative and significant effect on environmental disclosure. The company considered that it was no longer necessary to carry out environmental disclosure when the company has made a profit annually because the company’s environmental performance was good. Finally, leverage had a negative and significant effect on environmental disclosure. Thus, when the leverage of the company reached the maximum point, the company chose to pay off the debt, instead of conducting environmental disclosure.